African Development Indicators 2001 (The international Bank for Reconstruction and Development, 2001)
The report is intended to provide a consistent, and convenient set of data to monitor development programs, and aid flows in the Africa region, while continuing the succession of data publication series, began in 1989 by the World Bank, in cooperation with the United Nations Development Programme (UNDP). Each new volume provides access to more focused information, and represents an improvement in the quality, and availability of the data. The data contained in this report stems mostly, from national statistical services in Africa, and, additionally, many international agencies compile data on Africa, presented in a standardized framework. World Bank staff, supplement estimates to help address missing, or inconsistent data from standard sources, and, these differences in methodologies are addressed throughout in chapter introductions, and in technical notes. The report presents the available relevant data for 1970-99, grouped into fourteen chapters: background data; national accounts; prices, and exchange rates; money and banking; external sector; external debt, and related flows; government finance; sectoral information; aid flows; social indicators; and, environmental indicators (taken from the World Resources Institute's World Resources 2000).